The Meso-World: Tiny Publics and Political Action - Fine, Gary Alan (Qualitative Sociology Review, 2019)
In recent decades, sociologists have too often ignored the group level—the meso-level of analysis—in their emphasis on either the individual or the institution. This unfortunate absence misses much of what is central to a sociological analysis of community based on “action.” I draw upon Erving Goffman’s (1983) concept of the interaction order as I argue that a rigorous political sociology requires a focus on group cultures and tiny publics. Group dynamics, idiocultures, and interaction routines are central in creating social order. This approach to civic life draws from the pragmatism of John Dewey, as well as the broad tradition of symbolic interactionist theorists. Ultimately, I argue that a commitment to local action constitutes a commitment to a more extended social system.